From airwaves to earbuds: the rising influence of podcasts in modern communication / Muhammad Nabihan Abu Bakar and Masliya Yahya - Abu Bakar, Muhammad Nabihan; Yahya, Masliya (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
In today's fast-changing world, where each day feels like an urgent race to keep up, podcasting provides a wonderful opportunity to pause, listen, and connect. In this context, we see that people have always been fascinated by how they create and use culture to tackle challenges. Podcasting stands out as one of the transformative tools reshaping how we share ideas, amplify voices, and question existing media structures. It achieves this in ways we could not have foreseen even a decade ago. What causes podcasting so effective? First, it meets us exactly where we are. Unlike traditional media, podcasts do not require your undivided attention or a slot on your calendar. They integrate seamlessly with our lifestyles, whether we're on a long journey, working in the gym, or enjoying coffee on a calm morning. Podcasting is one of the most effective ways to express ideas and pique people's interest because of its versatility.